syntactic structure and Intonation Patterns in Absolute Interrogatives in spoken spa-nish in Cuba - Ramos Martín, Dania (Rastros Rostros, 2013)
This article is part of a study into lexical-syntactic inversion in absolute interrogative sentences in Cuban Spanish and their most common intonation patterns. As a starting point, the article uses previous results that confirm speakers’ tendency to maintain the linear order of sentence parts, and seeks to determine the communicative value that these expressions take on in discourse (colloquial), based on inter-level interaction and pragmatic conditions of use. A study of the sample (descriptive-explanatory type) found that interrogative expressions using intonation 3 (E3) can have various semantic-pragmatic uses